2019
DOI: 10.1101/784520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytosolic Ca2+modulates Golgi structure through PKC-mediated GRASP55 phosphorylation

Abstract: It has been well documented that the endoplasmic reticulum (ER) responds to cellular stresses through the unfolded protein response (UPR), but it is unknown how the Golgi responds to similar stresses. In this study, we treated HeLa cells with ER stress inducers, thapsigargin (TG), tunicamycin (Tu) and Dithiothreitol (DTT), and found that only TG treatment caused Golgi fragmentation. TG induced Golgi fragmentation at a low dose and short time when UPR was undetectable, demonstrating that Golgi fragmentation occ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…SARS-CoV-2 infection down-regulates GRASP55 but not its homolog GRASP65. GRASP55 has been shown to play a crucial role in various stress responses (Ireland et al, 2020b;Nüchel et al, 2021;Wang, 2018, 2020), while GRASP65 functions more in cell migration and apoptosis (Ahat et al, 2019;Bisel et al, 2008;Lane et al, 2002). In this study, we found that GRASP55 plays a vital role in viral infection, most likely related to its function in Golgi structure 13 formation.…”
Section: Discussionmentioning
confidence: 50%
“…SARS-CoV-2 infection down-regulates GRASP55 but not its homolog GRASP65. GRASP55 has been shown to play a crucial role in various stress responses (Ireland et al, 2020b;Nüchel et al, 2021;Wang, 2018, 2020), while GRASP65 functions more in cell migration and apoptosis (Ahat et al, 2019;Bisel et al, 2008;Lane et al, 2002). In this study, we found that GRASP55 plays a vital role in viral infection, most likely related to its function in Golgi structure 13 formation.…”
Section: Discussionmentioning
confidence: 50%